Effect of the inoculation of phosphate solubilizing bacteria on some charateristics of the Khang Dan rice cultivar - Ngoc Lan, Pham Thi; Lung, Truong Van (Academia Journal of Biology, 2015)
Effect of the inoculation of phosphate solubilizing bacteria on some charateristics of the Khang Dan rice cultivar